2015
DOI: 10.1097/md.0000000000001773
|View full text |Cite
|
Sign up to set email alerts
|

Enterohepatic Helicobacter Species as a Potential Causative Factor in Inflammatory Bowel Disease

Abstract: The Helicobacter species in the gut microbiota comprise Helicobacter pylori (H pylori) and enterohepatic Helicobacter species (EHS), which can colonize the intestinal mucosa. However, it is unclear whether EHS are associated with inflammatory bowel disease (IBD). Therefore, we conducted this meta-analysis to examine the association between EHS and IBD.PubMed, Scopus, Cochrane Library, and Web of Science databases, as well as abstracts from conference proceedings were searched to identify studies that used poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 48 publications
2
18
0
Order By: Relevance
“…Notably, inflammationpromoting OTUs related to Helicobacter, Peptostreptococcaceae, Streptococcus, and E. faecalis were increased in the stress-treated group. These findings fit well with evidence that Helicobacter is linked to IBD (42), as are Peptostreptococcaceae (43), Streptococcus (44), and E. faecalis (45). Lachnospiraceae, which has shown protection against colitis (46), were significantly decreased after stress.…”
Section: Discussionsupporting
confidence: 87%
“…Notably, inflammationpromoting OTUs related to Helicobacter, Peptostreptococcaceae, Streptococcus, and E. faecalis were increased in the stress-treated group. These findings fit well with evidence that Helicobacter is linked to IBD (42), as are Peptostreptococcaceae (43), Streptococcus (44), and E. faecalis (45). Lachnospiraceae, which has shown protection against colitis (46), were significantly decreased after stress.…”
Section: Discussionsupporting
confidence: 87%
“…The Helicobacter species in the gastrointestinal microbiota comprise Helicobacter pylori and enterohepatic Helicobacter species, which can colonize the intestinal mucosa. A recent meta‐analysis study indicated that the prevalence of Helicobacter species was higher among the patients with IBD, compared to controls . It appears that enterohepatic Helicobacter species was associated with IBD, while intestinal H. pylori infection was not significantly associated with IBD.…”
Section: Inflammatory Bowel Disease and The Gastrointestinal Tract MImentioning
confidence: 99%
“…were over-represented in colitis-induced Villin-Cre;Gankyrin f/f mice. Enterohepatic Helicobacter species (EHS) are known to colonize the intestine and are also associated with IBD [41]. In fact, the elevated abundance of EHS in IBD patients in comparison to healthy subjects was revealed by a meta-analysis based on 14 clinical studies [41].…”
Section: Discussionmentioning
confidence: 99%